Filsafat Pancasila Dalam Konsep Filosofis “Dalihan Na Tolu” Masyarakat Adat Batak Toba - Dian Uli Anatasia L Tobing, Bila May, Nadila Septiani Ritonga (Jurnal Pusat Studi Pendidikan Rakyat, 2023)
Dalihan Natolu is understood as an identity and way of life that regulates the kinship system and is a determining factor in Batak cultural customs. This paper has two objectives, namely: to seek and discover the philosophical foundations of Dalikan Natolu; and displays how Dalihan Natolu’s “das sollen” and “das sein” are in the “now” era. Dalihan Natolu is the embodiment of the nature of human life itself and is the result of the search for the meaning of life for the Toba Batak people. Dalihan Natolu is the embodiment of the nature of Debata Natolu (the three Gods). However, there have been shifts, deviations in values ??and changes in perspective regarding the positions of the three functional groups in Dalihan Natolu, namely Hulahula, Dongan Sabutuha, and Boru.